Kontribusi Pemikiran Pendidikan Az-Zarnuji Dalam Kitab Ta’limul Muta’allim - Satria Wiguna; Ahmad Darlis; Tsamrah Adawiah (Jurnal Dirosah Islamiyah, 2021)
Az-Zarnuji's educational concept in the book Ta'limul Muta'allim uses an Islamic education curriculum, Az-Zarnuji provides a simple but meaningful concept, that one must first achieve intellectual intelligence. The results of the study found that Az-Zarnuji's thoughts in the book Ta'limul muta'allim emphasized that in studying, he prioritized morals in learning and respected science, teachers, books, and society. Az-Zarnuji prioritizes morals in education to achieve goals, so as to achieve that goal, namely the success of the world and the hereafter. The type of research used is a qualitative research with a character study approach. The method of data collection is through literature study. Data analysis techniques by means of Descriptive Analysis and Content Analysis. Data analysis seeks to try to provide meaning that explains the form of explanation in the conclusion.